Hybrid compensation of polarization-multiplexed QPSK optical format for high bit rate networks - Omar Y. Shabaan; Omar A. Athab (Institute of Advanced Engineering and Science, 2020)
Transmitting the highest capacity throughput over the longest possible distance without any regeneration stage is an important goal of any long-haul optical network system. Accordingly, polarization-multiplexed quadrature phase-shift-keying (PM-QPSK) was introduced lately to achieve high bit-rate with relatively high spectral efficiency. Unfortunately, the required broad bandwidth of PM-QPSK increases the linear and nonlinear impairments in the physical layer of the optical fiber network. Increased attention has been spent to compensate for these impairments in the last years. In this paper, single mode fiber (SMF), single channel, PM-QPSK transceiver was simulated, with a mix of optical and electrical (digital signal processing (dsp) compensation stages to minimize the impairments The behaviour of the proposed system was investigated under four conditions: without compensation, with only optical compensator, with only DSP compensator and finally with both compensators. An evidence improvement was noticed in the case of hybrid compensation; where the transmission distance was multiplied from (720 km) to more than (3000 km) at 40 Gb/s.